Epidemiology of Injuries in the Radiology Department of a Teaching Hospital - C. Eze, Joseph; K. Nwodo, Victor; E. Ezugwu, Emmanuel; A. Agbo, Julius; Ikechukwu, Marvelous C.; C. Obasi, Favour (European Scientific Journal, ESJ, 2022)
Background: Injury has become a public health problem all over the world, and it is associated with high morbidity and mortality. Objective: This paper focuses on determining the epidemiology of injuries in the Radiology Department of Nnamdi Azikiwe University Teaching Hospital, Nnewi. Method: A retrospective research design was adopted for this study. Request forms of patients were collected from the register in the department. Five hundred and twenty (520) request forms were collected but twenty one (21) were excluded because they did not contain sufficient information needed for the study. The picture and archives communication system (PACS) was also utilized to ensure that information obtained from the register corresponds with the patients who took part within the period of the study. Data was analyzed descriptively using SPSS version 20. Results were presented in frequency tables and percentages. Results: The injuries involved 376 (75.2%) males and 123 (24.8%) females. Road traffic accident accounted for 67.5%, and it was the most occurring injury. Injuries due to fighting accounted for 2 (0.4%), which was the least occurring. Most injuries (18.8%) occurred within the age range of 21-30years, which was closely followed by the age range of 31-40 years (18.2%). Majority of the injuries involved the whole spine (18.5%), which is also followed by chest injuries (18.2%). Conclusion: The injuries recorded involved many body parts and more males than females were affected. Road traffic accident was the major cause of the injuries.